Application of Simplex Lattice Design Method on The Optimisation of Deodorant Roll-on Formula of Ashitaba (Angelica keiskei) - Wahida Hajrin; Windah Anugrah Subaidah; Yohanes Juliantoni; Dyke Gita Wirasisya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Ashitaba is known to have antioxidant activity and gram-positive antibacterial activity that causes body odor. This is the potential activity for an active substance to be developed as deodorant. The appropriate formula is needed, so it is necessary to optimize the formula using the right method. This study aimed was to determine the application of the simplex lattice design method on the optimization of a deodorant roll-on formula of ashitaba extract. Ashitaba was extracted by the maceration method. The formula optimization design was determined using the simplex lattice design method by Design ExpertÃÂ®7.5.1. The components for optimization were the concentration of carbopol and concentration of TEA, and the optimization parameters were the spreadability test, sticky power, and pH test. The optimum formula of deodorant consists of 0.45% carbopol and 2.05% TEA. The responses of optimum formula obtained spreadability test 6.32 ÃÂ± 0.33 cm, sticky power 44.67 ÃÂ± 3.94 seconds, and pH 7.73 ÃÂ± 0.17. These results meet the criteria for good preparation but need further testing related to the effectiveness of the preparation and the level of acceptance of the preparation by the user.